Electrolyte Performance of Noni Fruit Extracts (Morinda Citrifolia L.) for C-Zn Batteries - Akbar, Said Ali; Armelianda, Dilla; Muttakin, Muttakin (Universitas PGRI Madiun, 2018)
C-Zn battery is a commercial battery that widely used due to its easy to carry, inexpensive, and easy to obtain. However, the serious thing is the problem of battery waste which not only causes pollution but also endangers natural resources due to contained heavy metals (Mn) and corrosive electrolytes. Noni (Morinda citrifolia L.) is a fruit with the main component of vitamin C (ascorbic acid) as an antioxidant. This acid component is the basis for further utilization as an environmentally friendly electrolyte application. Noni was fermented with 2 time variations, 48 and 72 hours. Fabrication of C-Zn batteries was done with thin configurations like sandwiches. Furthermore, voltage was measured with digital multimeter. The results obtained, Open Circuit Voltage (OCV) of 0.72 V for unfermented electrolytes. Then, the use of fermented electrolytes causes an increase in voltage and current due to decreased pH.